2014
DOI: 10.1016/j.ydbio.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to chromium induces early reproductive senescence by increasing germ cell apoptosis and advancing germ cell cyst breakdown in the F1 offspring

Abstract: Hexavalent chromium (CrVI), one of the more toxic heavy metals, is widely used in more than 50 industries such as chrome plating, welding, wood processing and tanneries. As one of the world’s leading producers of chromium compounds, the U.S. is facing growing challenges in protecting human health against multiple adverse effects of CrVI. CrVI is rapidly converted to CrIII intracellularly, and can induce apoptosis through different mechanisms. Our previous studies demonstrated postnatal exposure to CrVI results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 67 publications
(90 reference statements)
0
29
1
Order By: Relevance
“…Many types of cells are known to undergo apoptosis in a p53-dependent manner in response to cytotoxic stimuli [42,4446]. Studies from our laboratory had clearly demonstrated potential roles for p53 pathway in CrVI-induced apoptosis through direct [39] and indirect [47] mechanisms in the ovary. A few studies have shown that more p53 protein is produced by the human placentas in abnormal pregnancies [48].…”
Section: Introductionmentioning
confidence: 99%
“…Many types of cells are known to undergo apoptosis in a p53-dependent manner in response to cytotoxic stimuli [42,4446]. Studies from our laboratory had clearly demonstrated potential roles for p53 pathway in CrVI-induced apoptosis through direct [39] and indirect [47] mechanisms in the ovary. A few studies have shown that more p53 protein is produced by the human placentas in abnormal pregnancies [48].…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic elimination of germ cells ultimately results in a reduced number of oocytes stored as primordial follicles within the ovary at birth (Myers et al 2014). Once formed, primordial follicles may be lost from the ovarian reserve as a consequence of exposure to endogenous and exogenous stressors, such as chemotherapy, radiation and environmental toxicants (Kerr et al 2012a, Sobinoff et al 2013, Sivakumar et al 2014. These agents are known to activate apoptotic responses within the primordial follicle oocyte itself, as well as in the granulosa cells of growing follicles (Suh et al 2006) (reviewed in Morgan et al (2012)).…”
Section: Introductionmentioning
confidence: 99%
“…CrIII increased cleaved Casp3 in the ovary. Our recent report also indicated that prenatal exposure to 25 ppm CrVI during the organogenesis window (gestational day 8.5-12.5) significantly up regulated cleaved Casp3 and apoptosis of germ cells and somatic cells on PND 1, whereas, it is not detectable in the control ovary [48]. Therefore, Casp3 -mediated cell death may be one of the key mechanisms for CrIII-induced increase in apoptosis in the ovarian cells followed by follicle atresia.…”
Section: Discussionmentioning
confidence: 88%